Atributos da Atenção Primária à Saúde da Criança: avaliação sob a ótica dos cuidadores - Araujo, Juliane Pagliari (2014)
Introduction: The Primary Health Care (PHC) is a strategy of organization and reorganization of the health system as well as the change in clinical care practice, constituting the first level of care. According to the theory postulated by Starfield, PHC is characterized by essential attributes: first contact access, longitudinality, comprehensiveness, and coordination of care, and derived attributes: family counseling, community orientation and cultural competence, which must be present in the service health so that this is really oriented PHC. From the evaluation of the presence and extent of the essential attributes and derived the PHC, have become consistent elements to identify the weaknesses of the system and guide the organization of health care services in production, specifically in this study, the population group zero to 12 years old. Objective: To evaluate the degree of orientation of the primary health care of the child in relation to the extension of the attributes of PHC. Methodology: This is a quantitative study, the evaluative. 548 interviews with caregivers of children younger than 12 years who were treated in 24 health units in the urban area of the city of Cascavel - PR were performed. The interviews were conducted by special act called Assessment Tool Primary - PCATool - Brazil child version , as well as by an instrument made by the research group, in relation to socioeconomic families. Data collection occurred from October 2012 and February 2013. Data were entered into a database created in Excel 2010 program, with double entry and checking of data for greater reliability, then sent to the software SPSS 17.0, the mean, standard error, minimum and maximum being calculated. Descriptive samples were presented as absolute and relative frequencies. For the bulk of the PHC score, the overall average of the attributes was calculated and divided by the number of attributes. For comparison of the presence and extent of attributes was used as cutoff values ≥ 6.6 scores, defined as high and values < 6.6 were considered low/unsatisfactory. Results: The data showed that the basic public health services of the city of Cascavel - PR, does not have guidance for PHC because the essential attributes and derivatives were not recognized in their full extent and caregivers of children using these services. The overall score of APS was 6,3, demonstrating the lack of guidance PHC for primary care to the child, not contributing to solving the healthcare provided. The access attribute of first contact had satisfactory mean score in the care process - using (8,6), however, on the structure of care - accessibility - score 5.5 points fragility in this attribute. The low score of the structure implies difficulties in children access to services, as well as deficiency of organizational structure and human resources for comprehensive care and quality focused on child health. The longitudinality also showed low score (6,1), indicating the difficulty of interaction between services and families of children over time, which implies a fragmented and poorly resolutive care. In the evaluation of integrated care services available and services produced unsatisfactory average scores (6,0 and 6,1 respectively). In this sense, there is a need to expand the services offered by the primary care for the child care may be resolving this point of attention. Essential attributes, the one to submit satisfactory scores on the structure (7,4) and the process (6,9) care referred to the coordination of care. Derived attributes - family orientation (4,4) and community orientation (5,1) had scores below the satisfactory, non integrating family and community in child care. Considerations: We can see the difficulty of guidance for PHC in health services measured by the lack of full extension of the APS attributes of care, strengthening the culture of curative care and focused on the individual. We emphasize the need for expansion of the Family Health Strategy services in the city, changing the process of care and assistance model, as well as the adoption of an integrated system of health services. Strengthening of PHC can result in better health of the child population, tending to reduce morbidity and mortality from preventable causes